HYBRID VERSION OF UKRAINE TRANSITION FROM PERIPHERY OF WORLD-ECONOMY TO SEMI-PERIPHERY - Баталов, О. А. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2021)
The article examines the transition of Ukraine from the periphery of the modern world-economy to the semi-periphery. Several global variants of such a transition have been analysed and a hybrid version has been proposed.Based on the analysis of Ukrainian export-import operations, the conclusion of our previous work of Ukraine being one of the periphery states has been confirmed. According to the global practice, for such states, there are two options for the transition to the semi-periphery. The first of them is the implementation of such systemic reforms that will allow for a considerable time to redistribute profits from international operations in their favour. This option is implemented in two forms. The first is authoritarian modernization (examples – Singapore, China). The second is reforms carried out with the broad support of the countries of the centre (an example is the European and Euro-Atlantic integration of the Central Europe countries). The second option is cooperation with the hegemonic state (USA) in the field of security and maintenance of order, for which such a state receives various support and access to the American sales market (examples - South Korea, Japan and the FRG, partly Turkey and Chile).It was concluded that the above options are unacceptable in a difficult Ukrainian case (chronic under-reforming, low quality of the Ukrainian elite, internal problems in the EU and the United States, a protracted conflict with the Russian Federation, etc.), thus there is a need for such an option that would combine the elements of all of the above – that is, a hybrid one. The proposed option assumes, firstly, the introduction of qualitatively new representatives into the Ukrainian elite, capable for systemic reforms, secondly, the continuation of European integration efforts, thirdly, strengthening cooperation with the United States in the security sphere, and fourthly, the activation of regional integration projects (primarily with Turkey and Poland). If efforts in one of the designated areas fail, then resources can be redirected to activate others without wasting precious time. As a conclusion, it was stated that the proposed hybrid version of Ukraine’s transition from the periphery to the semi-periphery looks like the only realistic way for Ukraine.